Feedback on Technical, Organizational, and Customer Service Skills of Employers of the Automotive Technology Graduates of One State University in the Philippines - John Michael Aquino; Jeffrey Garcia (MASI Mandiri Edukasi, 2023)
Employers' feedback on graduates' work productivity is critical for instructional designers, developers, and academic educators to produce new ideas for how graduates may fulfill their duties as citizens of dynamically varying companies. The findings of this study will be used to evaluate the automotive technology program and the basis for graduates' performance at work as it corresponds to technical practitioners, organizational skills, and customer service skills. The Sequential Mixed Method Design was used in the process of this study. The researcher utilized purposive sampling because the participants were determined with 42 employers and 88 LSPU-CIT automotive technology graduates from various firms that were the study's respondents. The researchers used a self-created survey-type questionnaire and a focus group discussion (FGD) interview guide to test the instrument's validity and reliability.Furthermore, respondents were asked to fill out a survey regarding how they rated a graduate's performance, and FGD was held to gain a broad and deep understanding of CIT Graduates' situations in their companies. Following the collection of all meaningful data, an experimental design was used. The findings revealed that the degree of feedback across employers in three domains was undeniable from the employers' perspective, as agreed in the in-depth conversation with the selected companies.